Hybrid assistive limb (HAL) treatment for patients with severe thoracic myelopathy due to ossification of the posterior longitudinal ligament (OPLL) in the postoperative acute/subacute phase: A clinical trial. (4th July 2019) - Kubota, Shigeki; Abe, Tetsuya; Kadone, Hideki; Shimizu, Yukiyo; Funayama, Toru; Watanabe, Hiroki; Marushima, Aiki; Koda, Masao; Hada, Yasushi; Sankai, Yoshiyuki; Yamazaki, Masashi
Abstract : Context/Objective: The hybrid assistive limb (HAL) is a wearable exoskeleton robot that assists walking and lower limb movements via real-time actuator control. Our aim was to clarify the safety and feasibility of using the HAL robotic suit for rehabilitation in patients with severe thoracic myelopathy due to ossification of the posterior longitudinal ligament (T-OPLL). Design: Uncontrolled case series; pre- and post-intervention measurement. Setting: In-patient rehabilitation unit. Intervention: HAL training was provided in 60-minuts session, 2–3 sessions per week, for a total of 10 sessions. HAL training was initiated on average 27.5 days post-surgery. Patients: Eight patients (four males and four females; mean age, 60.9 ± 10.2 years) with severe myelopathy, who had undergone posterior decompression with instrumented fusion, were enrolled. Outcome Measures: Gait speed, step length and cadence were measured along a 10-m walkway every session. The American Spinal Injury Association (ASIA) motor score (lower extremities) and Walking Index for Spinal Cord Injury (WISCI) II were also evaluated at baseline and after 10 sessions. The Japanese Orthopaedic Association (JOA) score was calculated over time after surgery. Results: All participants completed the 10 training sessions, with no serious adverse effect noted. Gait speed, step length and cadence improved over time. Both the WISCI-II and ASIA motor (lower extremities) scores improved from baseline after 10 sessions. The JOA score improved over time post-surgery. Conclusion: HAL training can be feasibly initiated in the early postoperative period, without severe adverse events in patients, with T-OPLL-related severe gait disturbance.